2009
DOI: 10.1590/s0101-20612009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Influência dos teores de aveia e de gordura nas características tecnológicas e funcionais de bolos

Abstract: A aveia (Avena sativa L.) destaca-se entre os cereais por fornecer aporte energético e nutricional equilibrado, conter em sua composição química aminoácidos, ácidos graxos, vitaminas e sais minerais indispensáveis ao organismo humano e, principalmente, pela composição de fibras alimentares (WEBER; GUTKOSKI; ELIAS, 2002).O uso de produtos de aveia como ingredientes na panificação é recomendável devido às suas propriedades funcionais tecnológicas, como a retenção de umidade, retardando com isso o envelhecimento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 5 publications
2
5
0
11
Order By: Relevance
“…Moisture levels of this study reached values close to those found in custom or specially-made cakes such as with addition of yacon flour (near 38%) (MOSCATTO; PRUDÊNCIO-FERREIRA; HAULY, 2004), oat fractions (between 26.4 and 32.6%) (GUTKOSKI et al, 2009), and whey (from 21.3 to 22.6%) (ZAVAREZE et al, 2010).…”
Section: Chemical Compositionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moisture levels of this study reached values close to those found in custom or specially-made cakes such as with addition of yacon flour (near 38%) (MOSCATTO; PRUDÊNCIO-FERREIRA; HAULY, 2004), oat fractions (between 26.4 and 32.6%) (GUTKOSKI et al, 2009), and whey (from 21.3 to 22.6%) (ZAVAREZE et al, 2010).…”
Section: Chemical Compositionsupporting
confidence: 76%
“…The increase in ash content is helpful to reach the daily mineral intake recommendation. In cakes prepared with addition of oats, the ashes content ranged between 1.8 and 2.9% (GUTKOSKI et al, 2009); and with yacon addition, the variation was from 1.6 to 1.9% (MOSCATTO; PRUDÊNCIO-FERREIRA;HAULY, 2004). Therefore, the ash content observed in this study are within the range found in other formulations.…”
Section: Chemical Compositionsupporting
confidence: 69%
“…These values were due to the fact that oats do not have the ability to form gluten, which is a characteristic unique to wheat fl our. However, its use in formulations is recommended, due to its functional properties and the quality of its proteins, which are appropriate from a nutritional standpoint (GUTKOSKI and PEDÓ, 2000).…”
Section: Technological and Functional Properties Of Dry Pastamentioning
confidence: 99%
“…The white oat (Avena sativa L.) is a cereal of excellent nutritional value with high levels of protein and dietary fi bre and an adequate amino acid composition according to FAO (Food and Agriculture Organization) (SIMIONI et al, 2007). As a functional food, oats can be used in commercial products with low caloric value and as a source of dietary fi bre (BUTT et al, 2008;GUTKOSKI et al, 2009;COLUSSI et al, 2013). It can also be used as a thickener due to its good stability against retrogradation (GALDEANO et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The oat used was composed of 50 % oat meal and 50% oat flakes. The oatmeal flakes differ from the oat meal flour by their larger grain size (GUTKOSKI et al, 2009). The mixture of flakes and oatmeal flour was used to provide a gradient of particle size seeking to better texture.…”
Section: Obtaining the Biscuitsmentioning
confidence: 99%